PACK CARBURIZING PADA SPROCKET SEPEDA MOTOR DENGAN MATERIAL BAJA KARBON RENDAH - Budi Hartono Setiamarga; Novi Kurniawati; Umen Rumendi (Mesin, 2006)
High quality motorcycle sprocket with cheaper price has been achieved by giving additional processing to non original locally made sprocket such that it has an almost the same quality as the original Japanese made sprocket . The additional processing was pack carburizing which was done to the non-original sprocket, followed by quench hardening and tempering so that the quality of the non-original sprocket will be almost the same as the original sprocket. Pack carburizing was applied with active carbon as the carbon source and 10% BaCO3 as the energizer. This process was done at 950°C and one hour holding time. For heat treatment, the heating was done at 850°C for 15 minutes, followed by water quenching and tempering at 150°C for 30 minutes. The carburizing result indicated that there was a carbon penetration depth of about 1.05 mm. After tempering, an effective case depth of about 0.2 mm was achieved. The process variables for obtaining an effective case depth of original sprocket (0.2 mm) are selected by applying pack carburizing using active carbon granule with 10%wt BaCO3 as the carburizing medium, processed at 950°C for an hour, followed by water quenching from 850°C and tempering at 150°C for 30 minutes.